Corrosion Resistance and Tribological Properties of Laser Cladding Layer of H13 Die Steel Strengthened by Ultrasonic Rolling - Kaikui Zheng; Youxi Lin; Jianguo Cai; Chengqian Lei (Chinese Journal of Mechanical Engineering, 2022)
Abstract Laser cladding is a new surface repair method that can improve the wear and corrosion resistance of substrate surfaces. However, the cladding layer typically exhibits a rough surface, high hardness and large residual tensile stress, and thus requires further machining and finishing. Ultrasonic rolling (U-rolling) is a highly efficient finishing and strengthening process that combines ultrasonic technology with traditional rolling (T-rolling). In this study, an iron-based alloy was coated onto the surface of H13 die steel using laser cladding, and the surface of the cladding layer was polished using U-rolling. The effects of U-rolling on the surface quality, corrosion resistance and friction and wear properties of the laser-cladding layer were investigated and compared with those obtained by T-rolling. The surface roughness of the U-rolled sample was only 1/4 that of the T-rolled sample. The hardness and residual compressive stress of the laser cladding layer after U-rolling were higher than those after T-rolling. Similarly, the surface corrosion resistance of the laser cladding layer after U-rolling was higher than that after T-rolling. U-rolling changed the surface roughness, grain size, and residual stress of the material and thus affected the corrosion resistance of the laser cladding layer. The friction coefficient and wear rate of the U-rolled surface of the cladding layer were lower than those of the T-rolled surface. In addition, the tribological properties of the cladding layer were found to be related to the rolling direction. When the friction direction of the sample was the same as the rolling direction, its friction and wear performance were higher than those when the two directions were perpendicular.